Effects of Baduanjin imagery and exercise on cognitive function in the elderly: A functional near-infrared spectroscopy study - Lianqiang Yao; Guoxiao Sun; Jun Wang; Yujuan Hai (Frontiers Media S.A., 2022)
ObjectiveCognitive function is essential in ensuring the quality of life of the elderly. This study aimed to investigate the effects of Baduanjin imagery and Baduanjin movement (a traditional Chinese health exercise, TCHE) on cognitive function in the elderly using functional near-infrared spectroscopy (fNIRS).Methods72 participants with a mean age of 66.92 years (SD = 4.77) were recruited for this study. The participants were randomly assigned to three groups: the Baduanjin imagery, the Baduanjin exercise, and the Control. Stroop task was used to record the accuracy and reaction times, and a near-infrared spectral brain imaging system was used to monitor the brain's oxy-hemoglobin concentration responses.Results(1) For the reaction times of Stroop incongruent tasks, the main effect of the test phase (F = 114.076, p < 0.001) and the interaction effect between test phase and group (F = 10.533, p < 0.001) were all significant. The simple effect analysis further demonstrated that the reaction times of the Baduanjin imagery group and Baduanjin exercise group in the post-test was faster than that in the pre-test (ps < 0.001); (2) Analysis of fNIRS data showed the significant interaction effect (F = 2.554, p = 0.013) between the test phase and group in the left dorsolateral prefrontal cortex. Further analysis showed that, during the post-test incongruent tasks, the oxy-Hb variations were significantly higher in participants of the Baduanjin imagery group (p = 0.005) and Baduanjin exercise group (p = 0.002) than in the control group; For the right inferior frontal gyrus, the interaction between the test phase and group was significant (F = 2.060, p = 0.044). Further analysis showed that, during the post-test incongruent tasks, the oxy-Hb variations were significantly higher in participants of the Baduanjin imagery group than in the control group (p = 0.001).ConclusionBaduanjin imagery and exercise positively affect cognitive performance; Baduanjin imagery and exercise activated the left dorsolateral prefrontal cortex; Baduanjin imagery activated the right inferior frontal gyrus, while Baduanjin exercise could not.